Medium energy, heavy and inert ion irradiation of metallic thin films: studies of surface nano‐structuring and metal burrowing. (15th March 2016) - Kumar, Pravin; Mal, Kedar; Kumar, Sunil; Sulania, Indra
Abstract : In context to the ion induced surface nanostructuring of metals and their burrowing in the substrates, we report the influence of Xe and Kr ion‐irradiation on Pt:Si and Ag:Si thin films of ~5‐nm thickness. For the irradiation of thin films, several ion energies (275 and 350 keV of Kr; 450 and 700 keV of Xe) were chosen to maintain a constant ratio of the nuclear energy loss to the electronic energy loss ( Sn /Se ) in Pt and Ag films (five in present studies). The ion‐fluence was varied from 1.0 × 10 15 to 1.0 × 10 17  ions/cm 2 . The irradiated films were characterized using Rutherford backscattering spectroscopy (RBS), atomic force microscopy (AFM) and scanning electron microscopy (SEM). The AFM and SEM images show ion beam induced systematic surface nano‐structuring of thin films. The surface nano‐structures evolve with the ion fluence. The RBS spectra show fluence dependent burrowing of Pt and Ag in Si upon the irradiation of both ion beams. At highest fluence, the depth of metal burrowing in Si for all irradiation conditions remains almost constant confirming the synergistic effect of energy losses by the ion beams. The RBS analysis also shows quite large sputtering of thin films bombarded with ion beams. The sputtering yield varied from 54% to 62% by irradiating the thin films with Xe and Kr ions of chosen energies at highest ion fluence. In the paper, we present the experimental results and discuss the ion induced surface nano‐structuring of Pt and Ag and their burrowing in Si. Copyright © 2016 John Wiley & Sons, Ltd.